Fracture analysis of steel fibre-reinforced concrete using Finite element method modeling - Shams, Muhammad Alamgeer; Bheel, Naraindas; Ali, Mohsin; Ahmad, Mahmood; Najeh, Taoufik; Gamil, Yaser; Almujibah, Hamad R.; Benjeddou, Omrane (Frontiers in Materials, 2024)
Concrete has a great capacity to withstand compressive strength, but it is rather weak at resisting tensile stresses, which ultimately result in the formation of cracks in concrete buildings. The development of cracks has a significant impact on the durability of concrete because they serve as direct pathways for corrosive substances that harm the concrete's constituents. Consequently, the reinforced concrete may experience degradation, cracking, weakening, or progressive disintegration. To mitigate such problems, it is advisable to include discrete fibres uniformly throughout the concrete mixture. The fibers function by spanning the voids created by fractures, therefore decelerating the mechanism of fracture initiation and advancement. It is not practical to assess the beginning and spread of cracks when there are uncertainties in the components and geometrical factors through probabilistic methods. This research examines the behaviour of variation of steel fibers in Fiber Reinforced Concrete (FRC) via Finite Element Method (FEM) modeling. In this study also the fracture parameters such as fracture energy, and fracture toughness have been computed through FEM analysis. The FEM constitutive model developed was also validated with the experimental result. The compressive strength of the developed constitutive model was 28.50MPa which is very close to the 28-day compressive strength obtained through the experiment i.e., 28.79MPa. Load carrying capacity obtained through FEM was 7.9 kN, 18 kN and 24 kN for three FEM models developed for three varying percentages of steel fiber 0.25%, 0.5%, and 0.75% respectively. The study developed a FEM model which can be used for calculating the fracture parameters of Steel Fibre-Reinforced Concrete (SFRC). Abbreviations FRC Fibre-Reinforced Concrete SFRC Steel fibre-Reinforced Concrete NLFEA Non-Linear Finite Element Analysis